RESILIENCE MODEL FOR THE EMPOWERMENT OF YOUNG COFFEE AGRIPRENEURS IN NAVIGATING BUSINESS ENVIRONMENT UNCERTAINTIES - Sri Sundari; Donny Agustinus Waluyo; Ahmad Ahsin Kusuma Mawardi (Universitas Sebelas Maret, 2025)
The resilience of entrepreneurial capacity was crucial for young agripreneurs in facing the challenges of uncertainty, such as climate change and economic fluctuations. Institutional capacity and the adoption of appropriate technology enabled adaptation and innovation, enhancing competitiveness and sustainability, although this relationship has not yet been explored in-depth. This study aimed to analyze the influence of environmental uncertainty on the resilience of young agripreneurs, with institutional capacity and the adoption of appropriate technology serving as mediating variables. This research utilized primary data collected through questionnaires distributed to 110 respondents, consisting of upstream-to-downstream coffee agripreneurs in Jember Regency, using purposive sampling. Data analysis was performed using SEM-PLS. The results showed that environmental uncertainty significantly influenced institutional capacity, the adoption of appropriate technology, and business resilience, with positive coefficients for all three and p-values below 0.05. Institutional capacity also positively affected the adoption of appropriate technology and business resilience. Moreover, institutional capacity moderated the impact of environmental uncertainty on the adoption of appropriate technology, while uncertainty, through institutional capacity and the adoption of appropriate technology, positively affected the resilience of young agripreneurs.